Effects of autumn diurnal freeze–thaw cycles on soil bacteria and greenhouse gases in the permafrost regions - Lv, Zhenying; Gu, Yuzheng; Chen, Shengyun; Chen, Jianwei; Jia, Yinglan (Frontiers in Microbiology, 2022)
Understanding the impacts of diurnal freeze-thaw cycles (DFTCs) on soil microorganisms and greenhouse gas emissions is crucial for assessing soil carbon and nitrogen cycles in the alpine ecosystems. However, relevant studies in the permafrost regions in the Qinghai-Tibet Plateau (QTP) are still lacking. In this study, we used high-throughput pyrosequencing and static chamber-gas chromatogram to study the changes in topsoil bacteria and fluxes of greenhouse gases, including carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O), during autumn DFTCs in the permafrost regions of the Shule River headwaters on the western part of Qilian Mountains, northeast margin of the QTP. The results showed that the bacterial communities contained a total of 35 phyla, 88 classes, 128 orders, 153 families, 176 genera, and 113 species. The dominant phyla were Proteobacteria, Acidobacteria, Actinobacteria, Chloroflexi, and Gemmatimonadetes. Two DFTCs led to a trend of increasing bacterial diversity and significant changes in the relative abundance of 17 known bacteria at the family, genus, and species levels. These were predominantly influenced by soil temperature, water content, and salinity. In addition, CO2 flux significantly increased while CH4 flux distinctly decreased, and N2O flux tended to increase after two DFTCs, with soil bacteria being the primary affecting variable.